Bimbingan dan Konseling Bidang Pribadi dan Sosial untuk Mengembangkan Penyesuaian Sosial Santri - Risnawanti Risnawanti; Mohammad Salehudin (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2022)
Every student is required to be able to adjust to the social environment. Social adjustment to students is not easy to do, this is due to various factors that result in students not being able to adjust to the social environment. The purpose of this research is to find out how the social personal guidance program is to develop students' social adjustment. This study uses a qualitative approach to the type of library research (library research). Social adjustment is a person's ability to be able to adjust to the environment where he lives. In overcoming the problems of social adjustment of students, social personal guidance programs can be used by counselors in dealing with problems of social adjustment. Social personal guidance is a service of guidance and counseling to be able to help overcome various problems that exist in individuals. It can be concluded that social private tutoring programs can help improve social adjustment in students by using various services contained in social private tutoring.